At the Heart of an Empire : The Royal Household in the Neo-Assyrian Period
This study is devoted to the Neo-Assyrian royal household as it emerges from the available cuneiform sources. It addresses the functions as well as the conditions of life and work of the royal household personnel. It clarifies which types of officials, professionals and other employees were active within or on behalf of the royal household. What were their tasks, and what was their position within the royal household and in relation to the king and his family? What departments were in place, and who were the managers? What was the role of lower-ranking personnel within this system? The study also investigates the social and cultural background of the personnel as well as their professional life, including their financial means, the quantity and type of their remuneration, and their career progression. Envisaged also as reference book, the book provides a prosopographical catalogue of the wide range of personnel discussed. As the personal household of the sovereign and the administrative and political centre of the empire, this study of the royal household opens up the immediate environment of the king and his family, but also to the governmental apparatus of the empire as a whole.